PENGARUH PENGATURAN MUKA AIR DAN PEMBERIAN ASAM AMINO TERHADAP PERTUMBUHAN DAN HASIL PADI - Eka Afriyan Hardigaluh; Radian Radian; Fadjar Rianto (Politeknik Pertanian Negeri Kupang, 2023)
Rice production technology that needs to be studied, in this study is water table regulation and amino acid administration. The study was conducted in Singkawang using a Complete Randomized Design. Two-factor factorial. The first factor regulates the height of the water table +5 cm, 0 cm, -10 cm, -20 cm. The second factor is administration without amino acids, synthetic amino acids 500 ppm, amino acids gold snails 500 ppm and 1000 ppm. The interaction of the two factors occurred in the variables of the number of productive saplings at the age of 42 hst, root volume and stem rigidity. The combination of water level treatment of -10 cm and the application of 500 ppm golden snail amino acids is the best with the number of saplings 38, the volume of roots as much as 50 ml and the rigidity of the stem in the category is rather strongKeywords: gold snail, productive tiller, inundation, stem rigidity, synthetic amino acids